2006
DOI: 10.1007/s10582-006-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of cesium transport through sand-bentonite mixtures

Abstract: The sorption and transport of Cs through mixture of Ca/Mg-bentonite and sand have been studied using five column experiments with different bentonite/sand ratio, initial Cs concentration and column height. For comparison the batch experiments with small m/V ratio and high Cs concentration were performed. The results showed that Cs removal from aqueous solution by bentonite is controlled by ion-exchange reaction between Cs and Ca/Mg initially sorbed on bentonite and that there is a consistency between the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Most of the researchers report us ing linear adsorption isotherm models [12] [10] [17] but som e employed nonlinear adsorption isotherm (Langmuir and Freundlich isotherms) [14] [15]. Few have studied the sp ecific radionuclide transport and adsorption on Nevada test soil despite the need for info rmation for the Nevada Test Site regulatory.…”
Section: Chi-wai Hui Buning Chen and Gordon Mckaymentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the researchers report us ing linear adsorption isotherm models [12] [10] [17] but som e employed nonlinear adsorption isotherm (Langmuir and Freundlich isotherms) [14] [15]. Few have studied the sp ecific radionuclide transport and adsorption on Nevada test soil despite the need for info rmation for the Nevada Test Site regulatory.…”
Section: Chi-wai Hui Buning Chen and Gordon Mckaymentioning
confidence: 99%
“…The aim of this study was to perf orm laboratory experiments using NTS soil and t o incorporate an "Advective Dispersion React ive model" [10] [24] [17] along with…”
Section: Chi-wai Hui Buning Chen and Gordon Mckaymentioning
confidence: 99%
See 2 more Smart Citations
“…Pb, Cd, Zn), cationic pollutants (e.g. dyes) from various wastes as well as for retention of RE, clay minerals were also used (Torstenfelt et al, 1982;Weiss et al, 1998;Kraus et al, 2006;Bergaya et al, 2006aBergaya et al, , 2006bKlika et al, 2007Klika et al, , 2011Vopálka et al, 2015). Uptake and factors influencing retention of La, Ce, Sm, Gd, Er, and Y on montmorillonite were investigated and it was found that montmorillonite in aqueous dispersion modifies their pH and therefore the precipitation of RE(III) hydroxides begins already at pH 5 (Bruque et al, 1980).…”
Section: Introductionmentioning
confidence: 99%